Problems of Muslim Society in Russia Past and Present - Meirison, Meirison; Bukhari, Bukhari; Wahab, Wisyly; Nazar, Zerly (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
This article aims to provide an overview of the Muslim minority in Russia not living in a homogeneous environment. The Muslim community in this country is facing old and new problems at the same time. Ancient in the sense that members of this community who identify themselves with Islam have inhabited this vast land for centuries. However, they are considered young because Muslims are part of the modern Russian state. This paper seeks to place the changes experienced by Muslims in Russian society in the context of an actual historical framework. Post-Soviet Union development centered on infrastructure, economy, and society. Now, at a crucial moment, is the time to push intra-Islamic relations to a higher level. Only this allowed Islam to become an integral part of Russia's political identity.